2016
DOI: 10.4103/2278-330x.179699
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship between histologic grades of invasive carcinoma of breast ducts and mast cell infiltration

Abstract: Introduction:Breast carcinoma is the most prevalent tumors among women. Transformation of inflated cells in immune response leads to increase in inflammatory cells such as macrophages, mast cells (MC) and fibroblasts. The aim of this study was to determine the relationship between grades of invasive carcinoma of the breast ducts and MC infiltration around tumoral cells.Methods:During the present study, 75 female patients suffering from invasive ductal carcinoma who underwent surgery or diagnostic biopsy during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…A recent study by Keser et al found that mast cells were present in all invasive primary tumors and in the metastatic lymph nodes [ 98 ]. In previous studies, mast cells were generally observed in the stroma adjacent to the neoplastic cells and near vascular structures [ 87 , 88 , 99 ]. Confusingly, while mast cells were detected in all metastatic lymph nodes, not all enlarged lymph nodes with evidence of immune reactivity (reactive lymph nodes) showed evidence of their presence.…”
Section: Mast Cells In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Keser et al found that mast cells were present in all invasive primary tumors and in the metastatic lymph nodes [ 98 ]. In previous studies, mast cells were generally observed in the stroma adjacent to the neoplastic cells and near vascular structures [ 87 , 88 , 99 ]. Confusingly, while mast cells were detected in all metastatic lymph nodes, not all enlarged lymph nodes with evidence of immune reactivity (reactive lymph nodes) showed evidence of their presence.…”
Section: Mast Cells In Breast Cancermentioning
confidence: 99%
“…Thus, peritumoral mast cells seem to contribute to breast cancer progression. Fakhrjou et al also found a positive association between the number of mast cells and the histopathological grade of the disease, particularly in invasive ductal carcinoma [ 99 ].…”
Section: Mast Cells In Breast Cancermentioning
confidence: 99%
“…The MC role in cancer progression is controversial; while some studies associate high tumor MC density with BrC subtypes of good prognosis or with favorable clinical outcomes [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], others find them associated with aggressive features [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. One potential problem of current approaches to elucidate the participation of MCs in BrC progression, is that most studies are observational and correlative, and until now the molecular mechanisms have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To treat patients with heterogeneous cancer, it is critical to understand the specific biological characteristics associated with the prognosis and outcomes of a given histological type. Approximately 83% of invasive breast cancers are classified as invasive ductal carcinoma, not otherwise specified (IDC-NOS) [2, 3], whereas approximately 0.1%~1% are defined as adenoid cystic carcinoma (ACC) [1, 3]. Based on its clinicopathological characteristics and outcomes, ACC is distinct from IDC-NOS.…”
Section: Introductionmentioning
confidence: 99%